Complete Sequences of Multiple-Drug Resistant IncHI2 ST3 Plasmids in Escherichia coli of Porcine Origin in Australia - Wyrsch, Ethan R.; Reid, Cameron J.; DeMaere, Matthew Z.; Liu, Michael Y.; Chapman, Toni A.; Roy Chowdhury, Piklu; Djordjevic, Steven P. (Frontiers in Sustainable Food Systems, 2019)
IncHI2 ST3 plasmids are known carriers of multiple antimicrobial resistance genes. Complete plasmid sequences from multiple drug resistant Escherichia coli circulating in Australian swine is however limited. Here we sequenced two related IncHI2 ST3 plasmids, pSDE-SvHI2, and pSDC-F2_12BHI2, from phylogenetically unrelated multiple-drug resistant Escherichia coli strains SvETEC (CC23:O157:H19) and F2_12B (ST93:O7:H4) from geographically disparate pig production operations in New South Wales, Australia. Unicycler was used to co-assemble short read (Illumina) and long read (PacBio SMRT) nucleotide sequence data. The plasmids encoded three drug-resistance loci, two of which carried class 1 integrons. One integron, hosting drfA12-orfF-aadA2, was within a hybrid Tn1721/Tn21, with the second residing within a copper/silver resistance transposon, comprising part of an atypical sul3-associated structure. The third resistance locus was flanked by IS15DI and encoded neomycin resistance (neoR). An oqx-encoding transposon (quinolone resistance), similar in structure to Tn6010, was identified only in pSDC-F2_12BHI2. Both plasmids showed high sequence identity to plasmid pSTM6-275, recently described in Salmonella enterica serotype 1,4,[5],12:i:- that has risen to prominence and become endemic in Australia. IncHI2 ST3 plasmids circulating in commensal and pathogenic E. coli from Australian swine belong to a lineage of plasmids often in association with sul3 and host multiple complex antibiotic and metal resistance structures, formed in part by IS26.